2022
DOI: 10.1038/s41598-022-13706-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome of Garcinia mangostana L. variety Mesta

Abstract: Fruits of Garcinia mangostana L. (mangosteen) are rich in nutrients with xanthones found in the pericarp having great pharmaceutical potential. Mangosteen variety Mesta is only found in Malaysia, which tastes sweeter than the common Manggis variety in Southeast Asia. In this study, we report the complete mitogenome of G. mangostana L. variety Mesta with a total sequence length of 371,235 bp of which 1.7% could be of plastid origin. The overall GC content of the mitogenome is 43.8%, comprising 29 protein-coding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…4 a), and 16 pair medium sized repeats between 120 and 920 bp in the P. serratifolia mitogenome (Supplementary Table S5 ). The distribution of repeat is consistent with many plant mitogenomes that have one or more pairs of large repeats 38 , 42 , 43 . Some reports showed that larger and medium-sized repeats can act as sites for inter- or intramolecular recombination, leading to multiple alternative arrangements or isoforms 42 , 43 .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…4 a), and 16 pair medium sized repeats between 120 and 920 bp in the P. serratifolia mitogenome (Supplementary Table S5 ). The distribution of repeat is consistent with many plant mitogenomes that have one or more pairs of large repeats 38 , 42 , 43 . Some reports showed that larger and medium-sized repeats can act as sites for inter- or intramolecular recombination, leading to multiple alternative arrangements or isoforms 42 , 43 .…”
Section: Resultssupporting
confidence: 81%
“…5 , the sequencing reads coverage of these repeats is similar to those of other non-repetitive sequences, which implies no branching nodes in each repeat. Therefore, P. serratifolia mitochondrial master genome assembly can be represented in the circular form, as previously reported in plant mitogenomes 20 , 38 , 44 . However, there is a total length of 88,247 bp between the two copies of the long repeats (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…ACG was used as a start codon in nad1 gene of P. pedunculata mitochondria directly, possibly due to a C-to-U conversion at the second site without editing in mitogenome ( Zandueta-Criado and Bock, 2004 ). RNA editing events were reported existing in the initiation codon of nad1 in other plants ( Li et al., 2018 ; Fang et al., 2021 ; Wee et al., 2022 ). Consistent to most plants, there is few RNA editing events occur in rRNA, tRNA and introns ( Giegé and Brennicke, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, two varieties of G. mangostana (Manggis and Mesta) were sequenced and deposited to GenBank [ 16 , 17 , 18 ]. The mitogenome of the Mesta variety was reported recently [ 19 ]. However, a complete analysis of the plastomes from these two varieties is yet to be reported.…”
Section: Introductionmentioning
confidence: 99%